2019
DOI: 10.1177/2396987318825484
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the prevalence of cognitive impairment no dementia in the first year post-stroke

Abstract: Introduction: Increasing attention is being paid to interventions for cognitive impairment (CI) post-stroke, including for CI that does not meet dementia criteria. The aim of this paper was to conduct a systematic review and meta-analysis of the prevalence of cognitive impairment no dementia (CIND) within one year post-stroke. Patients and methods: Pubmed, EMBASE and PsychInfo were searched for papers published in English in 1995-2017. Included studies were population or hospital-based cohort studies for first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 47 publications
7
110
0
3
Order By: Relevance
“…In our study, we found a high rate of CI after 90 days in general (80%), which is well above the expected prevalence in other studies (3,4,7). A selection-bias could occur due to the limited group size in this study: Only 10% of the patients treated in the GSR were finally given cognitive testing.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In our study, we found a high rate of CI after 90 days in general (80%), which is well above the expected prevalence in other studies (3,4,7). A selection-bias could occur due to the limited group size in this study: Only 10% of the patients treated in the GSR were finally given cognitive testing.…”
Section: Discussionsupporting
confidence: 53%
“…Even after good clinical recovery, about 30-50% of patients complain of cognitive impairment or dementia within the first year after an ischemic stroke (3)(4)(5)(6)(7). In the course, the prevalence of dementia even increases (8) with a broad spectrum of cognitive disturbances, ranging from mild cognitive impairment into a manifest dementia (9-12).…”
Section: Introductionmentioning
confidence: 99%
“…Most elderly people are requesting nursing care due to health conditions such as cognitive impairments that include dementia, Parkinson, blindness, etc. [13,14]. Though their chance of being admitted to a nursing home is low, modern technology, as well as methodology such as remote care, can assist to provide them with the needed nursing care at their residence place.…”
Section: What Is Nursing Care?mentioning
confidence: 99%
“…Stroke has been found to be a strong, independent and potentially modifiable risk factor for cognitive impairment and dementia [ 4 ]. It is estimated that, in the first year following stroke, 26.5% of stroke survivors have dementia, and 38% of survivors experience cognitive impairment that does not meet the criteria for dementia (cognitive impairment no dementia (CIND)) [ 5 , 6 ]. Yet post–stroke cognitive impairment (PSCI) is an often overlooked consequence of stroke [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%